Comparison of High-Efficiency MgO/Na2CO3 and MgO/K2CO3 as Heterogeneous Solid Base Catalysts for Biodiesel Production from Soybean Oil - Xiangyang Li; Xunxiang Jia; Weiji Li; Shufan Jia; Siwei Zhang; Jiliang Song; Jiao Wang (Molecules)
As a renewable alternative to fossil fuels, the industrial production of biodiesel urgently requires the development of efficient and recyclable solid base catalysts. In this study, the physicochemical properties and catalytic performance differences between MgO/Na2CO3 and MgO/K2CO3 catalysts were systematically compared using soybean oil as the raw material. By regulating the calcination temperature (500–700 °C), alcohol-to-oil ratio (3:1–24:1), and metal carbonate loading (10–50%), combined with N2 adsorption–desorption, CO2-TPD, XRD, SEM-EDS, and cycling experiments, the regulatory mechanisms of the ionic radius differences between sodium and potassium on the catalyst structure and performance were revealed. The results showed that MgO/Na2CO3-600 °C achieved a FAME yield of 97.5% under optimal conditions, which was 1.7% higher than MgO/K2CO3-600 °C (95.8%); this was attributed to its higher specific surface area (148.6 m2/g vs. 126.3 m2/g), homogeneous mesoporous structure, and strong basic site density. In addition, the cycle stability of MgO/K2CO3 was significantly lower, retaining only 65.2% of the yield after five cycles, while that of MgO/Na2CO3 was 88.2%. This stability difference stems from the disparity in their solubility in the reaction system. K2CO3 has a higher solubility in methanol (3.25 g/100 g at 60 °C compared to 1.15 g/100 g for Na2CO3), which is also reflected in the ion leaching rate (27.7% for K+ versus 18.9% for Na+). This study confirms that Na+ incorporation into the MgO lattice can optimize the distribution of active sites. Although K+ surface enrichment can enhance structural stability, the higher leaching rate leads to a rapid decline in catalyst activity, providing a theoretical basis for balancing catalyst activity and durability in sustainable biodiesel production.